Application Of Positive Affirmation Therapy To Overcome Situational Low Self-Esteem In Stroke Patients - Asep Riyana; Muhammad Azhar Alfarizi; Iwan Somantri; Ridwan Kustiawan (MEJORA Medical Journal Awatara, 2026)
The number of non-communicable diseases in Ciamis Regency is very high, with 3,140 cases recorded, including 57 stroke cases, where hypertension is the dominant contributing factor. Stroke patients frequently experience dependency in daily activities, leading to feelings of worthlessness and situational low self-esteem. Stroke is a condition caused by blockage or rupture of blood vessels in the brain, with impacts not only on physical functioning but also on psychological well-being. Positive affirmation therapy is a nursing intervention that aims to help patients recognize their abilities, improve their mindset, and increase self-confidence, making it a potential strategy for the psychosocial recovery of stroke patients. This study aims to describe the application of positive affirmation therapy in addressing situational low self-esteem among stroke patients at the Sindangkasih Health Center, Ciamis Regency. A descriptive qualitative method with a case study approach was used, involving two stroke patients with moderate situational low self-esteem, measured using a 30-item signs and symptoms instrument across five behavioral domains. The intervention was carried out for five consecutive days. The results showed that prior to the intervention, both patients presented with 17 signs and symptoms of situational low self-esteem, which decreased to 4 following the application of positive affirmation therapy. This case study concludes that positive affirmation therapy was effective in reducing signs and symptoms of situational low self-esteem in stroke patients and can be considered an alternative nursing intervention in primary healthcare settings. Patients are encouraged to independently practice the therapy at least twice daily to sustain improvements in self-esteem.